Analisis Dampak Program Pembangunan Desa terhadap Kesejahtraan Masyarakat (Desa Bonisari) - Muhamad Harom; Ambardi Ambardi; Yayat Sujatna (Lembaga Pengembangan Kinerja Dosen, 2025)
Village development is one of the main focuses in efforts to improve community welfare in Indonesia. Through Law no. 6 of 2014 concerning Villages, the government gives villages more authority to manage resources and implement development programs that suit the needs of local communities. This research aims to analyze the impact of village development programs on community welfare, using statistical data and relevant case examples. Using qualitative and quantitative approaches, this research reveals the relationship between the implementation of village development programs and improving community welfare, as well as the challenges faced in their implementation.